Penerapan Integrasi Model Waterfall dan User-Centered Design - Wulan, Sri Ratna; Hamida, Zahwa Putri; Kurniaty, Anna; Alifi, Muhammad Riza (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2024)
User-Centered Design (UCD) is a crucial approach in software development to ensure that the resulting product is user-friendly. However, the implementation of UCD within the software development lifecycle is still rarely discussed. This study aims to examine whether UCD can be integrated into the Waterfall model through the development of a web-based application. The integration process involves applying UCD during the requirements identification phase, followed by the other phases such as analysis, design, implementation, testing, and deployment. The research methods used include observation and interviews with the project implementers of the application development. The findings indicate that integrating UCD into the Waterfall model presents certain challenges, particularly due to the high risk of failure when the development phases do not allow returning to the initial phase that includes the UCD process. The interface evaluation conducted within the UCD process is proven to be crucial for the project's success.